The parameter space investigation method toolkit - Statnikov, R. B. (Roman Bent͡sionovich) (Artech House, 2011)
"The Parameter Space Investigation (PSI) method was developed to help engineers with a wide range of multicriteria optimization problems, such as design, identification, design of control systems, and operational development of prototypes. This unique resource shows you how to use PSI to construct a feasible solution set without limitations on the number of parameters and criteria. The book presents visualization tools that are used to construct the feasible solution set, conduct multicriteria analysis, and correct the initial problem statement."--Publisher's website